International Student Identities and Mental Well-Being Beyond the Single Story - Allen- Milton, Sharlene (Journal of Interdisciplinary Studies in Education, 2024)
Edited by Gudrun Nyunt, Katie Koo, Patty Witkowsky, & Mindy Andino, International Student Identities and Mental Well-Being Beyond the Single Story, provides valuable expertise and experience steeped in research, best practices, pertaining to the intersecting dimensions of  international students’ mental well-being for practitioners, faculty, counselors, and others working with international students at higher education institutions in the United States. International Student Identities and Mental Well-Being Beyond the Single Story is a timely book that unearths the longstanding mental health challenges, issues and concerns affecting international students . By interconnecting diverse perspectives and practical strategies, it challenges readers to rethink traditional approaches and embrace inclusive practices pertaining to international students. This book also aids in demystifying the topic of mental illness and allows safety in discussing issues affecting international students.